Congenital syphilis: associated factors in a follow-up outpatient clinic - Janer Aparecida Silveira Soares; Ana Paula Ferreira Holzmann; Bárbara Bispo da Silva Alves; Caio Fagundes Quadros Lima; Antônio Prates Caldeira (Revista Paulista de Pediatria, 2023)
Abstract Objective: This study aimed to describe the characteristics of mothers and children assisted in a follow-up clinic for congenital syphilis and identify the factors associated with the confirmation of the diagnosis. Methods: This is a prospective study conducted from 2016 to 2019 in Montes Claros, Northern Minas Gerais, Brazil. Specific forms addressing maternal sociodemographic, behavioral, and lifestyle habit characteristics, as well as characteristics related to access to healthcare, were used. Hierarchical Poisson regression analysis was performed to define the factors associated with diagnostic confirmation, including the calculation of the prevalence ratios (PR) and respective 95% confidence intervals (95%CI). Results: A total of 200 binomials (mother-child) who attended at least one appointment as part of the follow-up after discharge from the maternity hospital were eligible for the study. The mothers were mostly young (79.0%), with a low educational level (43.0%), and black (89.5%). Nearly half of the mothers reported not having a steady sexual partner (42.5%). About a quarter attended less than six prenatal appointments (27.5%). Nearly half did not treat the disease adequately during pregnancy (24.5%). The diagnosis of congenital syphilis was confirmed for 116 children. The following factors were associated with the diagnostic confirmation after multiple analyses: low maternal educational level (PR 1.30; 95%CI 1.05–1.60), maternal risky sexual behavior (PR 1.34; 95%CI 1.07–1.66), inadequate treatment of the mother (PR 3.16; 95%CI 2.42–4.47), and lack of treatment of the partner (PR 1.44; 95%CI 1,18–1.81). Conclusions: Syphilis remains a major challenge. The results highlight the social inequities associated with congenital syphilis and the lack of proper management of pregnant women and their partners.